Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

Effects of Shifts in Bacterial Community on Improving Water Quality and Growth Performance of Pacific Whiteleg Shrimp (Litopenaeus vannamei) in Biofloc Systems - Hai-Hong Huang; Chao Cheng; Li-Li Guo; Wan-Sheng Zou; Yan-Ju Lei; Wei-Qi Kuang; Bo-Lan Zhou; Pin-Hong Yang; Chao-Yun Li (Fishes, 2025)
This study aimed to induce a shift in a bacterial community by adding substrate into a biofloc system to characterize this shift and estimate its benefits in improving water quality and aquatic animal growth. We compared the bacterial communities between two biofloc systems, either with (sB treatment) or without (nB treatment) the addition of substrate (elastic solid packing filler), and we also analyzed the effects of the shift on the water quality and growth performance of shrimp (Litopenaeus vannamei). Beta diversity analysis indicated that the bacterial communities in the two treatments were significantly different (Jaccard index 0.94 ± 0.01, pseudo-F = 3.96, p = 0.001). The addition of substrate showed significant positive effects on bacterial alpha diversity indices (Shannon, Heip, Pielou, and Simpson; p

Monitoring for classical swine fever virus persistence and seropositivity in vaccinated pig farms using on-farm sentinel pigs during the pre-elimination phase toward a CSF-free status - Kuo-Jung Tsai; Hui-Yu Chen; Chun Wang; Chung-Shun Hung; Wei-Cheng Hsu; Tsu-Han Chen; Ming-Chung Deng; Cheng-Ta Tsai; Nien-Nong Lin; Jung-Pin Hsu; Chia-Yi Chang; Yu-Liang Huang (Preventive Veterinary Medicine, 2025)

System temperature prediction and verification of all-sky electrostatic analyzer on the lunar surface - Tsung-Pin Hung; Chih-Yu Chiang; Tzu-Fang Chang; Zhao-Yu Huang; Yu-Rong Cheng; Sheng-Cheng Tsai; Tzu-En Yen; Jih-Run Tsai; Shin-Fa Lin (Advances in Space Research, 2025)

Single-step pyrolytic synthesis of ultra-microporous ammonialized biochar for carbon dioxide capture - Che-Jung Hsu; I-Lin Kuo; Hsing-Cheng Hsi; Su Shiung Lam; Ying-Pin Huang; Yu-Chieh Ting (Journal of Environmental Management, 2025)

Estimating and characterizing spatiotemporal distributions of elemental PM2.5 using an ensemble machine learning approach in Taiwan - Chun-Sheng Huang; Kang Lo; Yee-Lin Wu; Fu-Cheng Wang; Yi-Shiang Shiu; Chu-Chih Chen; Yuan-Chien Lin; Cheng-Pin Kuo; Ho-Tang Liao; Tang-Huang Lin; Chang-Fu Wu (Atmospheric Pollution Research, 2025)

Dry solidification of chloride salts and heavy metals in waste incineration fly ash by mayenite - Xin Li; Dongdong Ge; Nanwen Zhu; Yukai Zong; Shi Cheng; Pin Zhou; Min Jiang; Yun Gu; Shouqiang Huang (Waste Management, 2025)

Unveiling the interaction and combined effects of multiple metals/metalloids exposure to TNF-α and kidney function in adults using bayesian kernel machine regression and quantile-based G-computation - Kuei-Hau Luo; Hung-Pin Tu; Yong-Chuan Chung; Min-Hsin Huang; Chen-Cheng Yang; Tzu-Hua Chen; Cheng-Hong Yang; Hung-Yi Chuang (Journal of Trace Elements in Medicine and Biology, 2024)

Investigation of space group effects of High-Voltage spinel LiNi0.5Mn1.5O4: Unveiling the influences of fluorinate benzimidazole salt additive - Chusnul Khotimah; Rio Akbar Yuwono; Fu-Ming Wang; Chun-Chen Yang; Nae-Lih Wu; Citra Deliana Dewi Sundari; Arif Cahyo Imawan; Ching-Kai Chang; Ping-Hsuan Hsu; Pin-Cheng Huang; Guan-Yi Liu; Yi-De Tsai; et al. (Chemical Engineering Journal, 2024)

Late Holocene paleoclimate reconstruction of northern Taiwan using a multiproxy approach in the Dream Lake sediment core - Abdur Rahman; Wei-Cheng Chang; Kaoru Kashima; Yu Fukumoto; Jyh-Jaan Steven Huang; Ludvig Löwemark; Liang-Chi Wang; Yuan-Pin Chang (Quaternary International, 2024)

Molecular simulation of the dynamic distribution of complex oil components in shale nanopores during CO2-EOR - Tao Huang; Linsong Cheng; Renyi Cao; Xiaobiao Wang; Pin Jia; Chong Cao (Chemical Engineering Journal, 2024)

Using recoverable sulfurized magnetic biochar for active capping to remediate multiple heavy metal contaminated sediment - Che-Jung Hsu; Yung-Hua Cheng; Adrienne Chung; Ying-Pin Huang; Yu Ting; Hsing-Cheng Hsi (Environmental Pollution, 2023)

Hypervalent potassium xanthate modified SnO2 for highly efficient perovskite solar modules - Pin Lv; Yufei Yang; Neng Li; Yuxi Zhang; Min Hu; Bo Huang; Yanqing Zhu; Yulong Wang; Junye Pan; Shifeng Wang; Bo Zhang; Fuzhi Huang; et al. (Chemical Engineering Journal, 2023)

Correction to: Receptor-Interacting Protein 140 Enhanced Temozolomide-Induced Cellular Apoptosis Through Regulation of E2F1 in Human Glioma Cell Lines - Hong-Chieh Tsai; Kuo-Chen Wei; Pin-Yuan Chen; Chiung-Yin Huang; Ko-Ting Chen; Ya-Jui Lin; Hsiao-Wei Cheng; Chun-Hao Huang; Hsiang-Tsui Wang (NeuroMolecular Medicine, 2022)

Receptor-Interacting Protein 140 Enhanced Temozolomide-Induced Cellular Apoptosis Through Regulation of E2F1 in Human Glioma Cell Lines - Hong-Chieh Tsai; Kuo-Chen Wei; Pin-Yuan Chen; Chiung-Yin Huang; Ko-Ting Chen; Ya-Jui Lin; Hsiao-Wei Cheng; Chun-Hao Huang; Hsiang-Tsui Wang (NeuroMolecular Medicine, 2022)

3D Step-by-step inversion strategy for audio magnetotellurics data based on unstructured mesh - San Cheng; Zhi-Yong Zhang; Feng Zhou; Man Li; Hui Chen; Fu-Sheng Shi; Lin-Pin Huang; Yong Li (Applied Geophysics, 2021)

Differential time-lag effects of ambient PM2.5 and PM2.5-bound PAHs on asthma emergency department visits - Shih-Chang Hsu; Jer-Hwa Chang; Chon-Lin Lee; Wen-Cheng Huang; Yuan-Pin Hsu; Chung-Te Liu; Shio-Shin Jean; Shau-Ku Huang; Chin-Wang Hsu (Environmental Science and Pollution Research, 2020)

The maize B chromosome is capable of expressing microRNAs and altering the expression of microRNAs derived from A chromosomes - Yen-Hua Huang; Shu-Fen Peng; Yao-Pin Lin; Ya-Ming Cheng (Chromosome Research, 2020)

Seasonal and diurnal variations of greenhouse gas emissions from a saline mangrove constructed wetland by using an in situ continuous GHG monitoring system - Cheng-Pin Tsai; Ching-Mei Huang; Chung-Shin Yuan; Lei Yang (Environmental Science and Pollution Research, 2020)

Particulates and particulates-bound mercury (Hg(p)) sizes (PM18, PM10, PM2.5, PM1, PM<1) distributions study by using MOUDI sampler at a complex sampling site - Guor-Cheng Fang; Chao-Lang Kao; Pin-Wen Huang; Huang-Min Chen; Yu-Lun Wu; Gui-Ren Liang (Environmental Geochemistry and Health, 2020)

Characterization and evaluation of Bacillus amyloliquefaciens strain WF02 regarding its biocontrol activities and genetic responses against bacterial wilt in two different resistant tomato cultivars - Chu-Ning Huang; Chan-Pin Lin; Feng-Chia Hsieh; Sook-Kuan Lee; Kuan-Chen Cheng; Chi-Te Liu (World Journal of Microbiology and Biotechnology, 2016)

A novel SMAD family protein, SMAD9 is involved in follicular initiation and changes egg yield of geese via synonymous mutations in exon1 and intron2 - Jun Xu; Jun Li; Haosen Wang; Guanglin Wang; Jie Chen; Pin Huang; Jienan Cheng; Lu Gan; Zhao Wang; Yafei Cai (Molecular Biology Reports, 2015)

Development of a loop-mediated isothermal amplification method for rapid detection of pigeon circovirus - Shinn Shyong Tsai; Yeng Ling Chang; Yen Li Huang; Hung Jen Liu; Guan Ming Ke; Chwei Jang Chiou; Yao Ching Hsieh; Tsung Chou Chang; Li Ting Cheng; Kuo Pin Chuang (Archives of Virology, 2014)

Genetic variations in TP53 binding sites are predictors of clinical outcomes in prostate cancer patients - Victor C. Lin; Chao-Yuan Huang; Yung-Chin Lee; Chia-Cheng Yu; Ta-Yuan Chang; Te-Ling Lu; Shu-Pin Huang; Bo-Ying Bao (Archives of Toxicology, 2014)

Proteomic and physiological analyses reveal detoxification and antioxidation induced by Cd stress in Kandelia candel roots - Zhao-Xia Weng; Ling-Xia Wang; Fang-lin Tan; Li Huang; Jian-Hong Xing; Shi-Pin Chen; Chi-Lien Cheng; Wei Chen (Trees, 2013)

Promising outcomes in glutaric aciduria type I patients detected by newborn screening - Chee-Seng Lee; Yin-Hsiu Chien; Shinn-Forng Peng; Pin-Wen Cheng; Lih-Maan Chang; Ai-Chu Huang; Wuh-Liang Hwu; Ni-Chung Lee (Metabolic Brain Disease, 2013)